2023
DOI: 10.3390/heritage6010030
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic Pozzolan from the Phlegraean Fields in the Structural Mortars of the Roman Temple of Nora (Sardinia)

Abstract: In this paper, we discuss the presence of volcanic pozzolans in the structural mortars of the Roman Temple of Nora in Sardinia (3rd c. AD), represented by pyroclastic rocks (pumices and tuffs) employed as coarse and fine aggregates. The provenance of these materials from the Phlegraean Fields was highlighted through a multi-analytical approach, involving Polarized Light Microscopy on thin sections (PLM), Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM-EDS), Quantitative Phase Analysis by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Long-term and durability studies of M-S-H cements are not reported in literature. However, M-S-H cements show a high resistance against carbonation [12,13] as also underlined by the observation of M-S-H in some Roman cements [41].…”
Section: Magnesium Silicate Cementsmentioning
confidence: 66%
See 1 more Smart Citation
“…Long-term and durability studies of M-S-H cements are not reported in literature. However, M-S-H cements show a high resistance against carbonation [12,13] as also underlined by the observation of M-S-H in some Roman cements [41].…”
Section: Magnesium Silicate Cementsmentioning
confidence: 66%
“…Magnesium from the seawater or clay water reacts with the amorphous silica from the degradation of C-S-H in cement leading to the formation of M-S-H [40]. M-S-H has also been observed in Roman cements rich in chert and dolostone [41] indicating a long-term stability of M-S-H. Electron microprobe, SEM/EDS and TEM analyses indicate that M-S-H contains not only magnesium, silica, hydroxides and water but that aluminium, calcium and iron can be incorporated in its structure [42,43].…”
Section: Magnesium Silicate Cementsmentioning
confidence: 99%
“…Since 2015, the University of Padova has been researching in the area of the Roman theatre of Aquileia (Comelli-Moro estates: Fig. 2: 6) (Ghiotto et al 2018;Ghiotto et al 2020;Ghiotto et al 2021;Dilaria et al 2023). 15 It is the latest of the main public buildings of 1 2 the Northern Adriatic city to be reliably identified, after some important hypotheses regarding its location had previously been put forward by archaeologist Luisa Bertacchi (Bertacchi 1995;Ghiotto 2019).…”
Section: Theatrementioning
confidence: 99%
“…This rock type, also known as "Pietra Tenera" (Soft Stone), refers to soft and easily workable limestones quarried in the Berici Hills, south of Vicenza. All the samples refer to the Oligocene Castelgomberto Limestone Formation [18] and they can be defined as grainstones, having a sparitic cement and abundant encrusting coralline Red Algae, ialyne foraminifera (nummulites and asterigerinids), bryozoans, serpulids and echinoids. The presence of benthonic miliolids foraminifera is relevant in the Costozza Stone variety (samples AD_74, Fig.…”
Section: A Sedimentary Rocksmentioning
confidence: 99%